2022
DOI: 10.3389/ffgc.2021.756678
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Lineage Distribution Modeling to Predict Epidemics of a Conifer Disease

Abstract: A growing body of evidence suggests that climate change is altering the epidemiology of many forest diseases. Nothophaeocryptopus gaeumannii (Rhode) Petrak, an ascomycete native to the Pacific Northwest and the causal agent of the Swiss needle cast (SNC) disease of Douglas-fir [Pseudotsuga menziesii (Mirbel) Franco], is no exception. In the past few decades, changing climatic conditions have coincided with periodic epidemics of SNC in coastal forests and plantations from Southwestern British Columbia (B.C.) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Two lineages of N. gaeumannii (lineage 1 c and 2) have been described on coastal Douglas-fir ( P. mensiezii var. mensiezii ); they have different levels of suitability to climates, increasing concerns that N. gaeumannii could rapidly adapt to environmental changes ( 6 , 7 ). A third lineage, lineage 1i, was recently identified on the Rocky Mountain variety of Douglas-fir ( P. mensiezii var.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Two lineages of N. gaeumannii (lineage 1 c and 2) have been described on coastal Douglas-fir ( P. mensiezii var. mensiezii ); they have different levels of suitability to climates, increasing concerns that N. gaeumannii could rapidly adapt to environmental changes ( 6 , 7 ). A third lineage, lineage 1i, was recently identified on the Rocky Mountain variety of Douglas-fir ( P. mensiezii var.…”
Section: Announcementmentioning
confidence: 99%
“…The germinating ascospore was transferred on 2% malt extract agar amended with 0.03% yeast extract (ME). Fungal cultures were then identified at the lineage level using the real-time PCR assay described in reference ( 7 ). Flasks with 125 mL ME broth were then inoculated with subsequent strains and incubated at 20°C with 200 rpm shaking for 4 to 5 weeks.…”
Section: Announcementmentioning
confidence: 99%
“…Recently, two major sympatric genetic lineages of N. gaeumannii were identified in the coastal Pacific Northwest. A distribution modelling approach suggested that the environmental tolerance range of lineage 1 exceeds that of lineage 2 and that lineage 1 should expand inland while distribution of lineage 2 should remain limited to its current range (Herpin‐Saunier et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…L1c and L2 are dominant and sympatric within coastal regions, with L1i being found in the interior. However, sequencing of contemporary and historical samples suggest that L1i has begun to supersede L2 along the British Columbia coastline, suggesting changing environmental suitability (Herpin-Saunier et al 2022). Despite studies showing a strong genetic differentiation between the lineages, and some support for reproductive isolation, there currently is insufficient evidence to support the two lineages being distinct biological species (Bennett and Stone 2019).…”
Section: Swiss Needle Cast (Snc) Is a Fungal Disease Of Douglas-fir T...mentioning
confidence: 99%